Regulação de procedimentos na escola pública: entre o centralismo formal e a apropriação informal - Luísa Veloso; Rufino, M.; Craveiro, D. (Sociologia, Problemas e Práticas, 2012)
The analysis examines and reflects on the way in which the work coordination processes in school organisations, namely in terms of the conception and planning of education, are set out in the external evaluation reports of schools and by their respective boards. It is based on information in the reports of the external evaluation of schools in three distinct regions of Portugal: Lisbon and the Tagus Valley, Alentejo and Algarve, and on interviews conducted with the governors of 20 schools. This approach sheds light on the ways in which the structuring processes are formalised; it also highlights the importance of the informal appropriation processes and mechanisms (reciprocal adjustment) that take place in both the construction and operationalisation of the formal regulation processes in the management of Portuguese schools (standardisation).